Coordination in Evolving Networks with Endogenous Decay - Francesco Feri; Miguel A. Meléndez-Jiménez (University of Innsbruck, Department of Public Finance, 2009)
This paper studies an evolutionary model of network formation with endogenous decay, in which agents benefit both from direct and indirect connections. In addition to forming (costly) links, agents choose actions for a coordination game that determines the level of decay of each link. We address the issues of coordination (long-run equilibrium selection) and network formation by means of stochastic stability techniques. We find that both the link cost and the trade-off between efficiency and risk-dominance play a crucial role in the long-run behavior of the system.
Keywords: C72; C73; D83; D85; 330; Coordination; Networks; Risk dominance; stochastic stability; Koordination; Soziales Netzwerk; Stochastischer Prozess; Nichtkooperatives Spiel; Evolutionäre Spieltheorie; Theorie